Formação inicial de professores de educação física a distância: aprendendo com a experiência do pró-licenciatura do Cefd/Ufes - Pozzatti, Mariana (2018)
Among the initiatives focused on teacher education in Brazil in the 2000s, the expansion of Distance Education (DE), a teaching modality offered by LDBEN n °. 9,394/1996. As a result for such expansion, the Physical Education and Sports Center of the "Federal University of Espírito Santo" offered the course "Pro-Licenciatura Phase II" from 2008 to 2014, project for 216 teachers associated with Physical Education in different municipalities of the State. In this work, we aim at understanding the political, institutional, curricular and epistemological dimensions of the aforementioned course, considering the specificity of such proposal and the lack of studies focusing on the investigated object. We discuss not only its present history, but we also turn our attention to its recent past (BLOCH, 2001). Our specific objectives are: a) conducting a review study of the teacher education in EaD in Brazil from 1997 to 2014; b) defining the concepts of distance education, teacher training, and Physical Education training as a basis for the discussions on the subject; c) contextualizing the aforementioned course, surveying the elements that led to its implementation and materialization; d) investigating how the actors involved in such training proposal have interpreted the formative processes of the course. e) highlighting the structuring elements of Physical Education teacher training in the distance modality, guaranteeing the specificities of this disciplinary knowledge area. In order to doing so, we base our research on the investigated experience, on the contributions and discussions of academic production in this field during the last decades, and on the theoretical design that underpins the structuring concepts of Technologies, Distance Education, Teacher Training and Teacher Training in Physical Education. We perform a qualitative study, based on the articulation among the bibliographical, documentary and field research. The two first ones address three main aspects: documents that constitute the analyzed course and its didactic material; academic production on Distance Teacher Training in Brazil; bibliographical survey about books and articles that explain the structuring fields of this research. The third deals with the participants of the training proposal and their relations and perceptions about the course, using the comprehensive interview as technique and method of work (KAUFMANN, 2013). We discuss the concepts of use, consumption, appropriation, strategies and tactics of Certeau (1995, 2009). We discuss teacher training within the profession based on Nóvoa (1992, 2002, 2004, 2007, 2009) and we understand the memories that have been brought into the reference memories of oral narratives produced by the participants based on Josso (2010). With the support of such interlocutors and the academic production of a special edition of Physical Education journal on teacher education in the sociocultural area, we address the specificities of the field and the ch allenge of thinking about distance learning. Finally, we conclude that the digital inclusion was the most significant learning from the course. In addition, we stress that the training proposal is relatively close to the egress profile that was origininally planned, but presents gaps regarding the function of forming with respect to the relation with knowledge in Physical Education, not reaching the idea of training within the profession that is defended as essential in the training of Physical Education teachers in the EaD modality.